Subwavelength Plasmonic Color Printing Protected for Ambient Use - Roberts, Alexander S; Pors, Anders; Albrektsen, Ole; Bozhevolnyi, Sergey I (Nano letters, 2014)
We demonstrate plasmonic color printing with subwavelength resolution using circular gap-plasmon resonators (GPRs) arranged in 340 nm period arrays of square unit cells and fabricated with single-step electron-beam lithography. We develop a printing procedure resulting in correct single-pixel color reproduction, high color uniformity of colored areas, and high reproduction fidelity. Furthermore, we demonstrate that, due to inherent stability of GPRs with respect to surfactants, the fabricated color print can be protected with a transparent dielectric overlay for ambient use without destroying its coloring. Using finite-element simulations, we uncover the physical mechanisms responsible for color printing with GPR arrays and suggest the appropriate design procedure minimizing the influence of the protection layer.